Assessing the viral content of uncultured picoeukaryotes in the global‐ocean by single cell genomics. Issue 18 (24th September 2019) - Castillo, Yaiza M.; Mangot, Jean‐François; Benites, Luiz Felipe; Logares, Ramiro; Kuronishi, Megumi; Ogata, Hiroyuki; Jaillon, Olivier; Massana, Ramon; Sebastián, Marta; Vaqué, Dolors
Abstract: Viruses are the most abundant biological entities on Earth and have fundamental ecological roles in controlling microbial communities. Yet, although their diversity is being increasingly explored, little is known about the extent of viral interactions with their protist hosts as most studies are limited to a few cultivated species. Here, we exploit the potential of single‐cell genomics to unveil viral associations in 65 individual cells of 11 essentially uncultured stramenopiles lineages sampled during the Tara Oceans expedition. We identified viral signals in 57% of the cells, covering nearly every lineage and with narrow host specificity signal. Only seven out of the 64 detected viruses displayed homologies to known viral sequences. A search for our viral sequences in global ocean metagenomes showed that they were preferentially found at the DCM and within the 0.2–3 µm size fraction. Some of the viral signals were widely distributed, while others geographically constrained. Among the viral signals we detected an endogenous mavirus virophage potentially integrated within the nuclear genome of two distant uncultured stramenopiles. Virophages have been previously reported as a cell's defence mechanism against other viruses, and may therefore play an important ecological role in regulating protist populations. Our results point to single‐cell genomics as a powerful tool to investigate viral associations in uncultured protists, suggesting a wide distribution of these relationships, and providing new insights into the global viral diversity.